2005
DOI: 10.1021/jf050145v
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin Metabolism in Rats and Their Distribution to Digestive Area, Kidney, and Brain

Abstract: Anthocyanins are present in human diet due to their wide occurrence in fruits and beverages. They possess antioxidant activities and could be involved in several health effects. The aim of this study was to investigate anthocyanin metabolism and distribution in the digestive area organs (stomach, jejunum and liver) and kidney, as well as a target tissue (brain) in rats fed with a blackberry (Rubus fruticosus L.) anthocyanin-enriched diet for 15 days. Identification and quantification of anthocyanin metabolites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
255
1
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 286 publications
(273 citation statements)
references
References 43 publications
14
255
1
3
Order By: Relevance
“…Furthermore, anthocyanins can be absorbed into the circulation in their intact form in small amounts, while substantial amounts of anthocyanins enter the colon and undergo extensive metabolic transformation by the gut microbiota, producing a wide range of aromatic and phenolic compounds (33). Several in vivo studies have shown that some of these compounds, such as protocatechuic acid (PCA), can be detected in the systemic circulation of rats and humans after consumption of the parent compounds (41). Notably, gut microbiota metabolites of anthocyanin may also contribute to the benefits of anthocyanin supplementation in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, anthocyanins can be absorbed into the circulation in their intact form in small amounts, while substantial amounts of anthocyanins enter the colon and undergo extensive metabolic transformation by the gut microbiota, producing a wide range of aromatic and phenolic compounds (33). Several in vivo studies have shown that some of these compounds, such as protocatechuic acid (PCA), can be detected in the systemic circulation of rats and humans after consumption of the parent compounds (41). Notably, gut microbiota metabolites of anthocyanin may also contribute to the benefits of anthocyanin supplementation in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, oral ingestion of pure epicatechin resulted in the detection of epicatechin glucuronide and 3 0 -O-methyl-epicatechin glucuronide in rat brain tissue [3]. Anthocyanidins have also been detected in the brain after oral administration [53,168], with several anthocyanidins being identified in different regions of rat brain after the animals were fed with blueberry [12]. Such flavonoid localisation has been correlated with increased cognitive performance, suggesting a central neuroprotective role of these components.…”
Section: Flavonoid Metabolism and Access To The Brainmentioning
confidence: 97%
“…Their brain entry may also depend on their interactions with specific efflux transporters expressed in the BBB, such as P-glycoprotein [63] which appears to be responsible for the differences between naringenin and quercetin flux into the brain in situ [135]. In animals, flavanones have been found to enter the brain following their intravenous administration [79], whilst epigallocatechin gallate [115], epicatechin [3] and anthocyanins [26,116] Fig. 1 The structures of the main classes of flavonoids.…”
Section: Absorption Metabolism and Distribution Of Flavonoidsmentioning
confidence: 99%